2022
DOI: 10.3389/fimmu.2022.840610
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Metabolism in Infection

Abstract: T lymphocytes (T cells) are divided into two functionally different subgroups the CD4+ T helper cells (Th) and the CD8+ cytotoxic T lymphocytes (CTL). Adequate CD4 and CD8 T cell activation to proliferation, clonal expansion and effector function is crucial for efficient clearance of infection by pathogens. Failure to do so may lead to T cell exhaustion. Upon activation by antigen presenting cells, T cells undergo metabolic reprograming that support effector functions. In this review we will discuss how metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 191 publications
(246 reference statements)
1
53
1
Order By: Relevance
“…When IAV infection occurs, monocytes and macrophages in the body accumulate in lung tissue and are activated; a large amount of IL-18 is matured and released outside the cells [ 56 , 57 ]. IL-18 can induce the production of IFN- γ by immune cells, activate NK cells, stimulate T cell proliferation, enhance the cytotoxic effect of lymphocytes, and induce the production of IFN- γ , IL-2, GM-CSF, and other cytokines by Th1 cells, leading to inflammation [ 58 62 ]. In our study, we also found that those three proinflammatory cytokines were dramatically elevated after IAV challenge.…”
Section: Discussionmentioning
confidence: 99%
“…When IAV infection occurs, monocytes and macrophages in the body accumulate in lung tissue and are activated; a large amount of IL-18 is matured and released outside the cells [ 56 , 57 ]. IL-18 can induce the production of IFN- γ by immune cells, activate NK cells, stimulate T cell proliferation, enhance the cytotoxic effect of lymphocytes, and induce the production of IFN- γ , IL-2, GM-CSF, and other cytokines by Th1 cells, leading to inflammation [ 58 62 ]. In our study, we also found that those three proinflammatory cytokines were dramatically elevated after IAV challenge.…”
Section: Discussionmentioning
confidence: 99%
“…After maturing at the primary site, T cells are transported to secondary immune organs, such as lymph nodes, spleen, appendix, tonsils, and adenoids, where T cells activate and differentiate into subpopulations of cells that perform immune functions (28). T lymphocytes can be divided functionally into two main subsets: CD4 + T helper cells (Th) and CD8 + cytotoxic T lymphocytes (CTL) (29). CD4 + T cells are indirectly involved in the clearance of infections by regulating the activity of other immune cells such as macrophages, neutrophils, B cells and CTL.…”
Section: Acquired Immune System: T Cell Implicationmentioning
confidence: 99%
“…TCR-CD3 is expressed on the surface of all T lymphocytes [ 18 ]. CD4 or CD8 are expressed on the surface of mature T cells and are divided into CD4+ T cells or CD8+ T cells [ 19 ]. Treg cells are a specific lineage of CD4+ T cells, which participate in maintaining immune homeostasis and restricting excessive immune responses, inhibiting the activation of primary T cells [ 12 , 20 ].…”
Section: Mechanism Of Inflammatory Response and T Cellmentioning
confidence: 99%